Comparison of the learning outcomes between flipped classroom and interactive lectures among medical undergraduates - Kurian, Simi; Mathews, Manu; Divakaran, Binoo (Asian Journal of Medical Sciences, 2025)
Background: Flipped classroom is a novel teaching-learning method which is more learner-centered. Here there is active involvement by students and more teacher-student interaction. Aims and Objectives: The study intends to compare the learning outcome of the flipped classroom method and interactive lectures among medical undergraduates and to determine the students’ perception of flipped classroom method. Materials and Methods: This was a non-randomized interventional study conducted in the Department of Obstetrics and Gynecology. Thirty-one students were exposed to flipped classrooms and 31 students to interactive lectures. Both the groups were assessed by a multiple choice question-based pre-test and post-test using the same questionnaire. At the end of 1 month after the intervention, another test was conducted to assess their retention of knowledge. The students’ perception of the flipped classroom was collected by a preformed validated questionnaire. Results: The average post-test score was higher for flipped classroom group compared to interactive lecture group and was statistically significant. The post-test score after 1 month was also significantly higher in flipped classroom group compared to the interactive lecture group. Majority of the students had strongly positive perception regarding flipped classroom and felt satisfied and motivated with flipped classroom. Conclusion: Based on our study, flipped classroom method is having better learning outcome than interactive lectures in terms of post-test scores as well as knowledge retention test scores after 1 month. Although flipped classroom was a new experience for the students, majority of the students were satisfied and felt more motivated.